Virtual economies in motion: integrating animated simulations and blockchain for immersive economic decision-making = Economías Virtuales en Movimiento: Integración de Simulaciones Animadas y Blockchain para Una Toma de Decisiones Económicas Inmersiva - RE, Ramel Yanuarta; Yahya, Norzariyah; Buan, Amelia; Lofandri, Wiki (AG Editor (Argentina), 2025)
The growing impact of digital transformation in economic education highlights the need for immersive, interactive, and transparent learning environments. Traditional teaching models often lack real-time simulations and verifiability, which limits learners’ ability to develop strategic thinking. This study addresses that gap by developing a blockchain-integrated animated simulation within a metaverse environment to enhance economic decision-making. A quantitative-exploratory design was employed, involving 45 postgraduate students in economics and information systems. The system used animated 3D simulations and blockchain transactions powered by smart contracts. Data collection instruments included a pre- and post-decision-making test and the System Usability Scale (SUS), with results analyzed using descriptive statistics and paired-sample t-tests. Findings revealed that 86,7 % of participants improved their decision accuracy, with an average SUS score of 83,1, indicating high usability. A paired-sample t-test showed a statistically significant improvement in decision accuracy from the pre-test (M = 62,5, SD = 9,4) to the post-test (M = 87,9, SD = 6,8), t (44) = 13,21, p < 0,001. These results confirm that immersive, blockchain-based simulations can enhance both economic understanding and learner engagement. The study suggests scalable applications in economic education, business training, and policy modeling.